The Influence of Openness on the Risk Management of "X" University Students Who Use Artificial intelligence in Malang City - Ajril Sabillah; Muchamad Adam Basori; Fathul Lubabin Nuqul (Psikoislamedia : Jurnal Psikologi, 2024)
This research was conducted with the aim of exploring the level of openness and risk management abilities possessed by "X" University students in Malang City regarding the development of artificial intelligence (AI) technology in the millennial era. Using a quantitative approach and probability sampling method, 377 respondents became research subjects. The research results show that the majority of students show a sufficient level of openness (78.26%), although their risk management towards AI tends to be high (47.5%). Further analysis revealed that openness had a significant influence on students' risk management abilities (p < 0.05). In conclusion, these findings highlight the need for a balanced approach between openness to innovative technology such as AI and awareness of the importance of risk management in dealing with its impact, especially for academic communities such as students at "X" University in Malang City.